Association between infant birth weight and gestational weight gain in Japanese women with diabetes mellitus - Kei Fujikawa Shingu; Masako Waguri; Mitsuyoshi Takahara; Aurélie Piedvache; Naoto Katakami; Iichiro Shimomura (Journal of Diabetes Investigation, 2024)
ABSTRACT Aims/Introduction In 2021, the guidelines on gestational weight gain (GWG) were revised and increased by 2–3 kg in Japan. This study aimed to investigate whether the revised guidelines would increase the incidence of babies with excessive birth weight in mothers with diabetes. Materials and Methods This retrospective study included 369 deliveries of women with diabetes whose pre‐pregnancy body mass index was below 30 kg/m2 between 1982 and 2021. The primary outcome measure was large for gestational age (LGA). We compared the incidence of LGA between women who gained weight within the previous guidelines and women who gained weight within the revised guidelines. We also compared the incidence of macrosomia, preeclampsia, small for gestational age (SGA), and low birth weight. Results The incidence of LGA was not significantly different between women who gained weight within the revised guidelines and those within the previous guidelines (34.6% [95% confidence interval 25.6–44.6%] for the revised guidelines vs 28.9% [21.6–37.1%] for the previous guidelines; P = 0.246). Neither was the incidence of macrosomia or preeclampsia significantly different (8.7% [4.0–15.8%] vs 5.6% [2.5–10.8%] and 5.8% [2.1–12.1%] vs 6.3% [2.9–11.7%]; P = 0.264 and 0.824, respectively), while women who gained weight within the revised guidelines had a lower incidence of SGA (1.9% [0.2–6.8%] vs 10.6% [6.0–16.8%]; P = 0.001) and low birth weight (1.0% [0.02–5.2%] vs 7.0% [3.4–12.6%]; P = 0.023). Conclusions The revised GWG guidelines could be beneficial in women with diabetes in terms of delivering babies with appropriate birth weight.